Experimental Evidence for Sildenafil's Action in the Central Nervous System: Dopamine and Serotonin Changes in the Medial Preoptic Area and Nucleus Accumbens During Sexual Arousal. (15th November 2012) - Kyratsas, Christos; Dalla, Christina; Anderzhanova, Elmira; Polissidis, Alexia; Kokras, Nikolaos; Konstantinides, Konstantinos; Papadopoulou‐Daifoti, Zeta
ABSTRACT Introduction. Sildenafil is the first effective oral treatment for male erectile dysfunction. Although it is generally accepted that its action is peripheral, it has been suggested that it influences central neural pathways that are involved in male sexual arousal. Recently, it was shown that local sildenafil administration enhances extracellular dopamine (DA) in the nucleus accumbens (NAcc). Aim. The aim of this study was to determine whether sildenafil administration alters dopaminergic and serotonergic activity in the NAcc and the medial preoptic area (mPOA) during a model of sexual arousal. Methods. An acute (2 days) or chronic (21 days) sildenafil regimen (1 mg/kg) was administered intraperitoneally to male rats. Thirty minutes after the last sildenafil injection, all males were exposed to noncontact erection sessions by the presentation of inaccessible estrous females. Half of the males had previous experience of noncontact sexual encounter and the other half were exposed for the first time. Main Outcome Measures. Tissue levels of DA and its metabolites, 3, 4‐Dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), as well as serotonin (5‐HT) and its metabolite 5‐HIAA, were measured in the mPOA and NAcc with high‐performance liquid chromatography with electrochemical detector. Dopamine ([DOPAC+HVA]/DA) and serotonin (5‐HIAA/5‐HT) turnovers were also calculated as indices of neurotransmission. Results. In nontrained males, acute and chronic sildenafil treatment increased DA and 5‐HT turnover rates in the mPOA and NAcc. In trained rats, acute sildenafil also increased DA and 5‐HT turnover rates in both structures, whereas chronic treatment enhanced 5‐HT turnover rate only in the mPOA and DA turnover rate only in the NAcc. Conclusions. Our data confirm that sildenafil enhances dopaminergic activity in the NAcc, extend these findings to the mPOA and furthermore, reveal sildenafil‐induced effects on serotonergic activity in these brain regions as well. Therefore, present findings support an effect of sildenafil on central neural pathways that are involved in the control of sexual arousal. Kyratsas C, Dalla C, Anderzhanova E, Polissidis A, Kokras N, Konstantinides K, and Papadopoulou‐Daifoti Z. Experimental evidence for sildenafil's action in the central nervous system: Dopamine and serotonin changes in the medial preoptic area and nucleus accumbens during sexual arousal. J Sex Med 2013;10:719–729.